Research 2015 : abstracts of research commissioned by National Research Council for Economics, Humanities and Social Sciences (NRCS) - Lee, Young-Soon [Verfasser] (My University, 2016)
This book is a compilation of abstracts from research projects conducted by the Korea Research Institute for Vocational Education and Training (KRIVET) in 2015. It aims to assist other related institutions and experts in the area to have a better understanding of technical education and training (TVET) in Korea. KRIVET is affiliated with the National Research Council for Economics, Humanities and Social Sciences (NRCS) under the Prime Minister's Office. The 2015 edition comprises descriptions of 37 projects and research activities. (BIBB-Doku)
Keywords: T 1 Forschungsrichtungen; I 2.3.4 Asien; Berufsbildungsforschung; KRIVET; Südkorea